The communication superhighway : social and economic change in the digital age - Hearn, Greg, 1957-; Mandeville, Tom.; Anthony, David (St Leonards, N.S.W. : Allen and Unwin, 1998)
The communication superhighway. Key areas of impact. Developing responses: philosophy, management and policy.
Keywords: Internet; Telecommunication systems; Social aspects; Economic aspects; Computer network; Telecommunication -- Economic aspects; Telecommunication -- Social aspects; Internet (Computer network) -- Economic aspects; Internet (Computer network) -- Social aspects